Guerra justa: uma análise teórica a partir do pensamento de João Calvino - Andrade, Daniel Justiniano (2008)
This research approaches the justification of the war starting from the point of view of the reformer John Calvin. Is the war fair or sacrilegious, divine or diabolical? Are the safety and the social justice, the individual freedom, the democracy, the equality, the social well-being guaranteed or done annihilate by the war? Does the thought of Calvin possess rational bases of what they justify the war and do they disqualify the religious fanaticism at the same time? Or will it be that his reasons for the war lead unavoidably to the unfaithful conversion for the fire and for the sword? Does it converge or diverge of the classic of the political science? Is it possible to find now in the countries heirs of the Calvino´s politics any likeness the essence of his thought? This research intends to answer these subjects. The starting point is the consideration of the narrow relationship among the several aspects of Calvino´s political theory and of these with certain details of his theology. The justifications of Calvin for the war, link with the authority reputed to the Bible and the history by him, the sovereignty and the providence of God, the existence of natural laws, the depravity of the mankind, the divine institution of the authorities and his duties and the legitimacy of the death penalty.